Faktor-Faktor yang Mempengaruhi Ketersediaan Beras Rumah Tangga Petani Rawa Lebak di Kecamatan Muara Belida Dimasa Pandemi Covid-19 - Andhika Mustika Rini; Yunita Yunita; Agustina Bidarti; Riswani Riswani (Pusat Unggulan Riset Pengembangan Lahan Suboptimal (PUR-PLSO) Universitas Sriwijaya, 2023)
Rini AM, Yunita Y, Bidarti A, Riswani R. 2022. Factors affecting the availability of rice households of tidal swamp farmers in muara belida district during the covid-19 pandemic. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal ke-10 Tahun 2022, Palembang 27 Oktober 2022. pp. 458-468. Palembang: Penerbit & Percetakan Universitas Sriwijaya (UNSRI).Covid-19 also affects the agricultural sector, including the availability of staple food for rice farmer households in Muara Belida District, Muara Enim Regency, which is a suboptimal land. This study aimed to analyze the factors of land area, production and total household income which are suspected to affect the availability of staple food rice for rice farmers in Muara Belida District, Muara Enim Regency during the covid-19 pandemic. The method used is a survey method, data collection is carried out directly through interviews using questionnaires. Data processing using multiple linear regression analysis techniques. The results of the analysis show that in Muara Belida District based on the value of the Coefficient of Determination (R2), it is known that land area, production and household income of rice farmers simultaneously have an effect of 22.9% on Food Availability of Rice Farmers' Household Rice while the rest is influenced by other factors outside the variable. researched. Based on the results of the Communal Test (Test F) it is known that jointly land area, production and total household income have a joint effect on the availability of rice food for rice farmer households in Muara Belida District. While the results of the partial test (T test) of land area and production partially have no effect on the availability of staple food rice for farmer households, while the total income of farm households has a partial effect on the availability of staple food for household farmers. Based on the results of the study, it can be concluded that there are other factors other than the variables of land area, production and total income of farm households that have a greater influence on the availability of rice for rice farmers of Lebak swamp rice farmers in Muara Belida sub-district during the Covid-19 pandemic.